2017
DOI: 10.1095/biolreprod.116.144691
|View full text |Cite
|
Sign up to set email alerts
|

Effects of in vitro exposure to dibutyl phthalate, mono-butyl phthalate, and acetyl tributyl citrate on ovarian antral follicle growth and viability†

Abstract: Dibutyl phthalate (DBP) is present in consumer products and the coating of some oral medications. Acetyl tributyl citrate (ATBC) has been proposed as an alternative to DBP because DBP causes endocrine disruption in animal models. Following ingestion, DBP is converted to its main metabolite mono-butyl phthalate (MBP) which has been detected in >90% of human follicular fluid samples. Previous studies show that DBP reduces the number of antral follicles present in the ovaries of mice. Thus, this study was designe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 35 publications
1
25
0
1
Order By: Relevance
“…In vitro studies of the effects of DBP exposure on Sertoli cell culture showed increased apoptosis stemming from inhibiting the PI3K/AKT and mTOR pathways which promote the proliferation and survival of sperm and the maintenance of testicular homeostasis [26]. Antral follicles isolated from female mice and exposed to DBP exhibited increased expression of the cyclin-dependent kinase inhibitors Cdkn1a and Cdkn2a and pro-apoptotic factors Bax and Bid along with down regulation of cyclin Ccnd2 resulting in growth inhibition and follicular death [28]. Permethrin has been shown to cause DNA damage in mitotic cells where exposure of peripheral blood mononuclear cells (PBMCs) induced breaks in the KMT2A and IGH genes which can be driver mutations for lymphoma and leukemia along with increased aneuploidy [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies of the effects of DBP exposure on Sertoli cell culture showed increased apoptosis stemming from inhibiting the PI3K/AKT and mTOR pathways which promote the proliferation and survival of sperm and the maintenance of testicular homeostasis [26]. Antral follicles isolated from female mice and exposed to DBP exhibited increased expression of the cyclin-dependent kinase inhibitors Cdkn1a and Cdkn2a and pro-apoptotic factors Bax and Bid along with down regulation of cyclin Ccnd2 resulting in growth inhibition and follicular death [28]. Permethrin has been shown to cause DNA damage in mitotic cells where exposure of peripheral blood mononuclear cells (PBMCs) induced breaks in the KMT2A and IGH genes which can be driver mutations for lymphoma and leukemia along with increased aneuploidy [36].…”
Section: Discussionmentioning
confidence: 99%
“…Higher levels have been detected in human urine, follicular fluid, and serum in different occupationally exposed groups [21,24]. In vitro and animal studies have shown that DBP disrupts the reproductive system resulting in inhibition of ovarian antral follicle growth and viability, altered gene expression in ovaries, testicular malformation and dysfunction, inhibition of spermatogenesis, and altered androgen signaling in males [2528]. In humans, a significant inverse relationship has been observed between levels of DBP metabolites (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Rasmussen et al investigated the effects of in vitro exposure to ATBC on ovarian antral follicle growth and viability [17]. At a dose of 0.01 μg/mL, ATBC increased the number of nongrowing follicles and terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL)-positive area in treated follicles, pointing to the possibility that ATBC may disrupt antral follicle function at low concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…DBP decreases growth of cultured mouse antral follicles, the last stage of ovarian follicle development before the preovulatory stage (Craig et al. 2013; Rasmussen et al. 2017).…”
Section: Description Of the Key Characteristics Of Female Reproductivmentioning
confidence: 99%
“…DBP causes arrest of follicle cells in the G1 phase of the cell cycle by up-regulating expression of cyclin-dependent kinase (CDK) inhibitors and down-regulating cyclins, resulting in decreased follicle growth (Craig et al. 2013; Rasmussen et al. 2017).…”
Section: Description Of the Key Characteristics Of Female Reproductivmentioning
confidence: 99%